Can empathy close the racial divide and gender gap in death penalty support?. (10th January 2019) - Godcharles, Brian D.; Rad, Jordyn D.J.; Heide, Kathleen M.; Cochran, John K.; Solomon, Eldra P.
Abstract: Public opinion data indicate that the majority of US respondents support the death penalty. Research has consistently indicated, however, that Blacks and females are significantly less likely to support capital punishment than their White and male counterparts. Past research efforts attempting to account for these differences have, at best, only partially accounted for them: the racial divide and gender gap in death penalty support, while narrowed, remained evident. This study proposes that empathy, particularly ethnocultural empathy, may be a key explanatory correlate of death penalty support and that racial and gender differences in empathy may fully explain the observed racial and gender differences in death penalty support. This study uses three forms of empathy measures (cognitive, affective, and ethnocultural) to test this hypothesis using survey data from a sample of undergraduate students. Our results show that neither a variety of other "known correlates" of death penalty support nor cognitive or affective empathy scales were able to fully account for the observed racial difference in death penalty support. Ethnocultural empathy, however, was successful in reducing the effect of race on death penalty support to nonsignificance. To the best of our knowledge, this is the first study to have done so.